FLUKTUASI EKSPOR CRUDE PALM OIL (CPO) INDONESIA KE INDIA PASCA RATIFIKASI ASEAN-INDIA FREE TRADE AGREEMENT (AIFTA) - Annisa Prima Bernaz; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This paper is a Bilateral Trade study that provides analysis of the cooperation of two countries in the fulfillment of needs and achieve their nasl interests. This research focused on the fluctuation of export CPO Indonesia to india after ratification AIFTA. Crude Palm Oil (CPO) is the result of processed pulp of palm fruits as vegetables oil which is needed as the world largest producer of palm oil contributes 51% to the world’s palm oil demand and engages in esxport to varioud countries including India.This paper uses a conceptual basis, with the concept of international cooperation where here international cooperation is formed because of international life covering various fields such as ideology,politics, economy,social culture, environment and security defense.Supported by National Nation’s analysis level and liberalism perspective. The concept leads to qualitative methds and field studies and is assisted by literature studies as a source of information. The cooperation carried out by ASEAN with India provides significant benefits for Indonesia's CPO exports. Where India is one of the largest CPO importing countries from Indonesia. therefore, of course there are many factors that can cause the export of cpo to india from Indonesia to experience gains or decreases which have an impact on both countries Keywords: AIFTA, Cooperation, Liberalism Perspective, Exports, Fluctuations